Regional Differences and Financial Ratios: A Comparative Approach on Companies of ISE City Indexes - DERAN, Ali; ISKENDEROGLU, Omer; ERDURU, Incilay (International Journal of Economics and Financial Issues, 2014)
This study aims to compare the regional differences by the financial ratios of 157 companies listed on Istanbul Stock Exchange (ISE), Turkey. In this respect, data of 157 companies are researched on the city indexes of Istanbul, Izmir, Kocaeli and Bursa. 16 ratios showing liquidity, financial structure, turnover, profitability and stock market performance of the companies is calculated in the analysis for 2011 annually. Independent Sample t test and Mann-Whitney U Test are employed to reveal any significant difference in the companies operating in different regions. The result of the study varies on the compared regions. The differences also figure out that financial management differs among regions. Keywords: financial ratio; regional difference; independent sample t test;mann-whitney u test JEL Classifications: B26; L25; M41